2021
DOI: 10.1063/5.0064535
|View full text |Cite
|
Sign up to set email alerts
|

Discharge and plasma plume characterization of a 100 A-class LaB6 hollow cathode

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Through the experimental and simulation analysis of the cathode-independent working process by Domonkos et al [30], Mikellides et al [31], combined with test results under coupled cathode and thruster conditions by Li et al [32], Albarède et al [10], Goebel et al [14], Manzella et al [19,20], Mazouffre et al [33] and others, showed that as the cathode flow rate decreases, ∆V c increases and the CEES deteriorates. Therefore, in this study, the method of changing the cathode working gas flow rate was used to simulate the working conditions under which the CEES was deteriorated.…”
Section: Experimental Setup and Measurementmentioning
confidence: 99%
“…Through the experimental and simulation analysis of the cathode-independent working process by Domonkos et al [30], Mikellides et al [31], combined with test results under coupled cathode and thruster conditions by Li et al [32], Albarède et al [10], Goebel et al [14], Manzella et al [19,20], Mazouffre et al [33] and others, showed that as the cathode flow rate decreases, ∆V c increases and the CEES deteriorates. Therefore, in this study, the method of changing the cathode working gas flow rate was used to simulate the working conditions under which the CEES was deteriorated.…”
Section: Experimental Setup and Measurementmentioning
confidence: 99%